Republication of “Stress Fractures of the Foot and Ankle in Athletes” - Philip B. Kaiser MD; Daniel Guss MD, MBA; Christopher W. DiGiovanni MD (Foot & Ankle Orthopaedics, 2023)
Stress fractures of the foot and ankle are common injuries in athletes. Management differs considerably based on fracture location and predisposing factors. Repetitive loading of the foot and ankle in athletes should result in physiologic bone remodeling in accordance with Wolff’s law. However, when there is not sufficient time for complete healing to occur before additional loads are incurred, this process can instead lead to stress fracture. Assessment of the athlete’s training regimen and overall bone health is paramount to both the discovery and treatment of these injuries, although diagnosis is often delayed in the setting of normal-appearing initial radiographs. While most stress fractures of the foot or ankle can usually be treated nonoperatively with a period of activity modification, fractures in certain locations are considered “high risk” due to poor intrinsic healing and may warrant more proactive operative management.